The Effectiveness Of Meaningful Instructional Design Learning Model In Learning To Write Poster Students Of Class Viii Smp Negeri 32 Oku - Awalludin Awalludin; Rita Nilawijaya (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
This research aims to (1) to know the ability of VIII students of SMP Negeri 4 OKU to write posters before and after using the meaningful instructional design model and (2) to know the effectiveness of instructional model Meaningful Instructional Design in writing poster of student of class VIII SMP Negeri 32 OKU. The method used in this research is the experimental method with One Group Pretest-Posttest Design. The sample of the research is class VIII B totaling 36 people. Technique of data collection using essay test. Data analysis using statistical technique with t-test formula (t-test). The results showed that on pretest writing posters, students who scored 56-65 amounted to 11 people, students who scored 46-55 amounted to 21 people, students who get the value of 00-45 amounted to 4 people with an average value of 55 or less category . On posttest writing posters, students who score 80-100 amounted to 20 people, students who get 66-79 amounted to 9 people, students who get 56-65 amounted to 7 people with an average of 74.58 or good category. Based on the calculation, 5% significant level of writing poster known t-table 2.00 and t-count 15,53, t-count bigger than t-table (15,53 2,00). Thus, it can be concluded that the instructional model Meaningful Instructional Design effectively used in learning posters writing students of class VIII SMP Negeri 32 OKU.Keywords: effectiveness, meaningful instructional design, learning, writing, poster